PLACE BRAND MANAGEMENT IN DOWNTURNS: A THEORETICAL FRAMEWORK - jawahar, deepa jawahar; e n, anju (Revista de turism - studii și cercetări în turism, 2020)
In recent times the tourism industry has become an important source of income and also key economic growth indicator across the world. The tourism industry is also highly vulnerable to natural and man-made calamities. Over the years, media coverage of the disaster has conveyed the resulting loss of life, human suffering, public and private property damage, economic and social disruption. This period between the disaster and restoration of normalcy can be defined as a tourism crisis for a tourist destination which can threaten the normal operation and conduct of tourism allied business. This paper tries to explore the strategies used by companies to market their products at the time of economic downturn, which can be applied in a place brand context in the tourism sector. The study has utilized the concept of place brand equity to explain the situation and strategy because brand equity is the actual valuation and the perception of a brand. An extensive literature review has been conducted to identify the marketing strategies of branded consumer products at the time of economic downturns and is explained from the lenses of various dimensions of place brand equity.